Slurry composition for negative electrode for secondary battery

By adding carbon nanotubes and carboxymethyl cellulose with specific properties to the negative electrode slurry composition for lithium ion secondary batteries, the problem of difficult to take into account both the stability and conductivity of the coating liquid, and a negative electrode with high stability and low resistance value is achieved, which is suitable for the manufacturing of lithium ion batteries.

CN119678263APending Publication Date: 2025-03-21MITSUBISHI PENCIL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380058509.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-31
Filing Date
2023-10-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing slurry composition for negative electrodes for lithium-ion secondary batteries has problems that are difficult to take into account both the stability of the coating liquid and the conductivity, and is insufficient dispersion, long dispersion, and easy to peel off during electrode processing.

Method used

The negative electrode slurry composition for secondary batteries containing at least carbon nanotubes, conductive materials, negative electrode active substances, dispersants and binder components is used, and the viscosity and stability are adjusted by using carboxymethyl cellulose with a mass average molecular weight of 300,000 or less, or its metal salt with a mass average molecular weight of 1 million to 3 million.

Benefits of technology

Even if a negative electrode slurry composition for secondary batteries using carbon nanotubes is realized, a negative electrode with high stability and low resistance value can be formed, and is suitable for battery/electrode production such as lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005264447950000131
    Figure BDA0005264447950000131
Patent Text Reader

Abstract

Provided is a slurry composition for a negative electrode for a secondary battery, which is suitable for the production of a battery / electrode such as a lithium ion battery capable of forming a negative electrode having high stability and a low resistance value when the electrode is formed, even when the slurry composition is a slurry composition for a negative electrode for a secondary battery using carbon nanotubes. This slurry composition for a negative electrode for a secondary battery is characterized by containing at least carbon nanotubes, a conductive material, an active material for a negative electrode, a dispersant, and a binder component, and the dispersant is composed of a carboxymethyl cellulose having a mass average molecular weight of 300,000 or less or a metal salt thereof, and a carboxymethyl cellulose having a mass average molecular weight of 1,000,000 to 3,000,000 or a metal salt thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This specification relates to a slurry composition for a negative electrode for secondary batteries suitable for production of electrodes / batteries such as lithium ion batteries. Background Art

[0002] With the popularity of electric vehicles, the miniaturization, lightness and high performance of portable devices such as mobile phones and notebook personal computers, secondary batteries with high energy density and high capacity are required. In this context, lithium-ion secondary batteries using non-aqueous electrolytes are gradually being used in a large number of devices due to their high energy density and high voltage. Polyvinylpyrrolidone (PVP) has been often used as a dispersant in the past.

[0003] This polyvinyl pyrrolidone (PVP) has a disadvantage that the resistance value increases when added. By not using PVP, the resistance value can be reduced. In recent years, carboxymethyl cellulose and the like which have little influence on the resistance value have been used.

[0004] As an example of a conventional negative electrode composition for lithium ion secondary batteries, carboxymethyl cellulose is used, for example,

[0005] 1) Patent document 1 discloses a method for manufacturing a lithium secondary battery, characterized in that it is a method for manufacturing a lithium secondary battery having a negative electrode having a negative electrode collector and a negative electrode composite material layer formed on the negative electrode collector, the method comprising the following steps: a step of dispersing a negative electrode active material and a binder containing at least carboxymethyl cellulose (CMC) in a solvent to prepare a slurry-like composition; a step of applying the prepared slurry-like composition to the negative electrode collector to form the negative electrode composite material layer; and a step of constructing a lithium secondary battery using the negative electrode having the negative electrode composite material layer formed thereon, wherein as the carboxymethyl cellulose (CMC), a low molecular weight region CMC having a weight average molecular weight of less than 1 million and a high molecular weight region CMC having a weight average molecular weight of more than 3 million are used in such a manner that the weight ratio (A:B) of the low molecular weight region CMC (A) to the high molecular weight region CMC (B) is 25:75 to 75:25;

[0006] 2) Patent document 2 discloses a method for manufacturing a negative electrode plate for a non-aqueous electrolyte secondary battery, the manufacturing method comprising the following kneading process: a negative electrode active material formed of a graphite material that absorbs / releases lithium ions, a thickener and a binder are dispersed or dissolved in water to adjust a slurry-like coating composition, characterized in that the kneading process is the following process: a first thickener having a viscosity of 1 wt % aqueous solution in the range of 10 to 1800 mPa·s and the negative electrode active material are dispersed in the presence of water, and then a second thickener having a viscosity of 1 wt % aqueous solution in the range of 3000 to 10000 mPa·s is added and dispersed, and then a binder is added;

[0007] 3) Patent document 3 discloses a negative electrode plate for a non-aqueous secondary battery, characterized in that it is a negative electrode plate for a non-aqueous secondary battery, characterized in that a negative electrode mixture coating in which an active material formed by a material capable of retaining at least lithium, a bonding material and a thickener are mixed and dispersed in a dispersion medium is attached to a negative electrode collector to form a negative electrode mixture layer, and the thickener is composed of a first carboxymethyl cellulose with a low viscosity and a high degree of etherification and a second carboxymethyl cellulose with a high viscosity and a low degree of etherification (for example, refer to patent document 3); etc.

[0008] On the other hand, recently, carbon nanotubes have been used as negative electrode materials for lithium ion secondary batteries by using carbon nanotube dispersions or the like, due to their excellent conductivity, ability to reduce electrode resistance, ability to efficiently form a conductive network with a small amount, and the like.

[0009] For example, Patent Document 4 discloses a slurry as a negative electrode mixture slurry for a non-aqueous electrolyte secondary battery, wherein surface-modified natural graphite as an active material, a carbon nanotube dispersion, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) as a binder component (adhesive) are dispersed in water.

[0010] The above-mentioned Patent Document 1 discloses the use of carboxymethyl cellulose (CMC) as a binder component and uses high molecular weight CMC, and its purpose and technical concept are different from those of the present disclosure.

[0011] When carbon nanotubes are contained in the negative electrode slurry composition for secondary batteries using the two types of carboxymethyl cellulose (CMC) used in Patent Documents 2 and 3, it is difficult to achieve a balance between the stability of the coating solution and the conductive performance after coating.

[0012] Patent Document 4 discloses a secondary battery negative electrode slurry composition using a carbon nanotube dispersion having specific physical properties, but there are problems such as insufficient dispersion, time-consuming dispersion, and peeling during electrode processing, and further improvements are urgently needed.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Publication No. 2013-89422 (claims, examples, etc.)

[0016] Patent Document 2: Japanese Patent Application Publication No. 2009-99441 (claims, examples, etc.)

[0017] Patent Document 3: Japanese Patent Application Publication No. 2012-59488 (claims, examples, etc.)

[0018] Patent Document 4: Japanese Patent Application Publication No. 2015-195143 (claims, examples, etc.) Summary of the invention

[0019] Problem that the invention aims to solve

[0020] The present disclosure is made in order to solve the above-mentioned conventional problems, and its purpose is to provide a slurry composition for a negative electrode for a secondary battery that is suitable for battery / electrode manufacturing such as lithium ion batteries that can form a negative electrode with high stability and low resistance when the electrode is formed, even if it is a slurry composition for a negative electrode for a secondary battery using carbon nanotubes.

[0021] Solutions for solving problems

[0022] The present inventors have conducted intensive research on the above-mentioned existing problems and found that a slurry composition for a negative electrode for a secondary battery containing at least carbon nanotubes, a conductive material, an active material for a negative electrode, a dispersant, and a binder component, and that a slurry composition for a negative electrode for a secondary battery suitable for the above-mentioned purpose of manufacturing a battery / electrode such as a lithium ion battery, is obtained by using two types of carboxymethyl cellulose having specific physical properties as the above-mentioned dispersant, thereby completing the present disclosure.

[0023] That is, the slurry composition for negative electrode for secondary battery disclosed in the present invention is characterized in that it contains at least: carbon nanotubes, conductive material, negative electrode active material, dispersant and binder component, and the aforementioned dispersant is carboxymethyl cellulose or its metal salt with a mass average molecular weight of less than 300,000 and carboxymethyl cellulose or its metal salt with a mass average molecular weight of 1 million to 3 million.

[0024] The slurry composition for the negative electrode of the secondary battery preferably has a shear rate of 1000 s -1 The viscosity is 0.1 to 1.5 Pa·s.

[0025] Effects of the Invention

[0026] According to the present disclosure, a negative electrode slurry composition for a secondary battery can be provided, which can form a negative electrode with high stability and low resistance when the electrode is formed, and is not easily separated during storage over time, and is suitable for the production of batteries / electrodes such as the above-mentioned lithium ion batteries.

[0027] The objects and effects of the present disclosure can be realized and achieved particularly by using the constituent elements and combinations pointed out in the claims.Both the above general description and the following detailed description are exemplary and explanatory and do not limit the present disclosure described in the claims. DETAILED DESCRIPTION

[0028] The following describes the embodiments of the present disclosure in detail. However, the scope of protection of the present disclosure is not limited to the embodiments described in detail below, and it should be noted that it involves the inventions and their equivalents recorded in the claims. In addition, the present disclosure can be implemented based on the contents disclosed in this specification and the technical common sense in the field (including conventional technical selection and obvious features).

[0029] The slurry composition for negative electrode of secondary battery disclosed in the present invention is characterized in that it contains at least: carbon nanotubes, conductive material, negative electrode active material, dispersant and binder component, and the above-mentioned dispersant is carboxymethyl cellulose or its metal salt with a mass average molecular weight of less than 300,000 and carboxymethyl cellulose or its metal salt with a mass average molecular weight of 1 million to 3 million.

[0030] 〈Carbon Nanotube (CNT)〉

[0031] The carbon nanotubes (CNTs) used in the present invention are not particularly limited as long as they have a cylindrical shape formed by essentially winding one surface of graphite. Any single-layer CNT obtained by winding one surface of graphite into one layer or multilayer CNT wound into two or three or more layers can be used.

[0032] In addition, examples of carbon nanotube forms include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers, but are not limited to these and may be any of these alone or in combination of two or more (hereinafter referred to as "at least one").

[0033] Furthermore, from the viewpoints of the viscosity, conductivity and stability of the dispersion, the average outer diameter of the carbon nanotubes is preferably 1 nm to 90 nm, more preferably 3 nm to 30 nm, and even more preferably 3 nm to 15 nm.

[0034] In the present disclosure, the average outer diameter of carbon nanotubes refers to the arithmetic mean of a sufficient number n of outer diameters measured using an image at a magnification of 100,000 or more using a transmission electron microscope.

[0035] The purity of the carbon nanotubes used in the present disclosure is preferably 90 to 100% by mass, particularly preferably 95 to 100% by mass. The purity of the carbon nanotubes is calculated based on the amount of impurities, ash content measured in accordance with JIS K 1469 and JIS K 6218.

[0036] As carbon nanotubes (CNT) that can be specifically used, for example, NC7000 (average outer diameter 10 nm) manufactured by Nanocyl, Baytubes C150P (average outer diameter 11 nm) manufactured by Bayer, FloTube9000 (average outer diameter 19 nm), FloTube7320 (average outer diameter 9 nm), FloTube7010 (average outer diameter 9 nm), FloTube6810 (average outer diameter 8 nm), FloTube6120 (average outer diameter 8 nm), FloTube6100 (average outer diameter 8 nm), FloTube2020 (average outer diameter 4 nm) manufactured by Cnano, MEIJOeDIPS EC2.0 (average outer diameter 2.0 nm) manufactured by Meijo Nanocarbon CO., LTD., KORBON-A7 (average outer diameter 1.2 nm) manufactured by KORBON, KOATSU GAS At least one of NFT-7 (average outer diameter 30 nm) manufactured by KOGYO CO., LTD., NFT-15 (average outer diameter 30 nm) manufactured by KOATSU GAS KOGYO CO., LTD., and the like.

[0037] The content of these carbon nanotubes (CNT) can be set to a suitable content, and is not particularly limited. Ideally, in order to take into account both high stability and conductive performance, and the preferred coating liquid viscosity, its content relative to the total amount of the slurry composition is preferably set to 0.1 to 15.0 mass %, further preferably to 0.1 to 10.0 mass %, more preferably to 0.1 to 8.0 mass %, 0.1 to 6.0 mass %, and particularly preferably to 0.1 to 5.0 mass % is ideal.

[0038] When the content of the carbon nanotubes (CNT) is 0.1% by mass or more, sufficient conductivity can be ensured, while when the content is 15.0% by mass or less, stability of the coating liquid and good conductivity can be ensured.

[0039] 〈Conductive materials〉

[0040] Examples of conductive materials other than the carbon nanotubes (CNTs) include graphene, graphite, and carbon particles such as carbon black such as acetylene black and Ketjen black. These can be used alone or in combination.

[0041] The shape of these carbon particles is not particularly limited, and may be, for example, flat, array-like, spherical, or the like.

[0042] The average particle size of these carbon particles can be more than 100nm, more than 200nm, more than 300nm, more than 500nm, more than 700nm, more than 1μm, more than 2μm or more than 3μm, and can be less than 20μm, less than 15μm, less than 10μm or less than 7μm. Here, the average particle size used in this specification is appropriately selected according to the size of the carbon particles to be targeted. In the case of particles roughly less than 1μm, it is the value of the histogram average particle size (D50) based on the scattering intensity distribution measured by the dynamic light scattering method. In the case of particles above 1μm, it is the value of the median particle size (D50) calculated by the volume basis in the laser diffraction method. The determination based on the dynamic light scattering method can be carried out, for example, using DelsaMax CORE (Beckman Coulter). The determination based on the laser diffraction method can be carried out, for example, using the particle size distribution measuring device MT3300II (MicrotracBEL Corp.).

[0043] The content of these conductive materials can be set to a suitable content, and is not particularly limited. Ideally, in order to take into account both high stability and conductive performance, and the preferred coating liquid viscosity, the content is preferably set to 0.1 to 15.0 mass %, more preferably 0.1 to 10.0 mass %, more preferably 0.1 to 8.0 mass %, 0.1 to 6.0 mass %, and particularly 0.1 to 5.0 mass % relative to the total amount of the slurry composition.

[0044] (Active material for negative electrode)

[0045] The negative electrode active material that can be used is not particularly limited, and for example, metal oxide-based active material particles, silicon-based active material particles, and particularly metal oxide-based negative electrode active material particles can be used.

[0046] As metal oxide-based negative electrode active material particles, for example, titanium oxide can be used. As titanium oxide, there is no particular limitation as long as it can absorb and release lithium, for example, spinel lithium titanate, ramsdellite lithium titanate, titanium-containing metal composite oxides, titanium dioxide (TiO2(B)) having a monoclinic crystal structure, and anatase titanium dioxide can be used.

[0047] As spinel lithium titanate, Li4+xTi5O 12 (x varies within the range of -1≤x≤3 due to the charge-discharge reaction), etc. Examples of ramsdellite-type lithium titanate include Li2+yTi3O7 (y varies within the range of -1≤y≤3 due to the charge-discharge reaction), etc. Examples of TiO2(B) and anatase-type titanium dioxide include Li1+zTiO2 (z varies within the range of -1≤z≤0 due to the charge-discharge reaction), etc.

[0048] As the titanium-containing metal composite oxide, there can be mentioned a metal composite oxide containing Ti and containing at least one element selected from the group consisting of P, V, Sn, Cu, Ni and Fe, etc. As the metal composite oxide containing Ti and containing at least one element selected from the group consisting of P, V, Sn, Cu, Ni and Fe, there can be mentioned, for example, TiO2-P2O5, TiO2-V2O5, TiO2-P2O5-SnO2, TiO2-P2O5-MeO (Me is at least one element selected from the group consisting of Cu, Ni and Fe), etc.

[0049] Such a metal composite oxide has low crystallinity, and preferably has a microstructure in which a crystalline phase and an amorphous phase coexist, or an amorphous phase exists alone. The microstructure can further improve the cycle performance.

[0050] In the negative electrode slurry composition for secondary batteries of the present disclosure, the content of the negative electrode active material is preferably 30 to 60 mass %, more preferably 35 to 55 mass % based on the total amount of the negative electrode slurry in order to ensure battery capacity and fluidity of the slurry.

[0051] (Dispersant)

[0052] The dispersants used in the present disclosure are (A) carboxymethyl cellulose (CMC) or its metal salt having a mass average molecular weight of 300,000 or less and (B) carboxymethyl cellulose (CMC) or its metal salt having a mass average molecular weight of 1 to 3 million. By using carboxymethyl cellulose (CMC) or its metal salt having a combination of these properties [(A) and (B)] in combination, the effect of the present disclosure is exerted for the first time. As metal salts, sodium salts, ammonium salts, etc. can be cited. Sodium salts are preferred.

[0053] The “mass average molecular weight” in the present disclosure can be calculated by measuring an aqueous solution by gel permeation chromatography.

[0054] Specifically, as the CMC or its metal salt having the above-mentioned mass average molecular weight having the above-mentioned characteristics, any commercially available product can be used. Examples of the commercially available product of (A) include CELLOGEN WS-C manufactured by DKS Co., Ltd. (mass average molecular weight 150,000: sodium salt), Daicel 1220 manufactured by Daicel Corporation (mass average molecular weight 300,000: sodium salt), and F01MC manufactured by Nippon Paper Industries, Ltd. (mass average molecular weight 200,000: sodium salt). Examples of the commercially available product of (B) include F150LC manufactured by Nippon Paper Industries, Ltd. (mass average molecular weight 2,000,000: sodium salt), and Daicel 1190 manufactured by Daicel Corporation (mass average molecular weight 1,800,000: sodium salt).

[0055] Combinations other than the above (A) and (B), that is, when the above (A) or (B) is used alone, (X) CMC or its metal salt having a mass average molecular weight of more than 300,000 to less than 1,000,000, and (Y) CMC or its metal salt having a mass average molecular weight of more than 3,000,000 are used alone, or in combination types based on these (X), (Y), and the above (A), (B), stability and conductive performance may be lacking, which is not preferred.

[0056] The mass ratio of the low mass average molecular weight (A) to the high mass average molecular weight (B) is preferably 1:0.1 to 1:4, particularly preferably 1:0.3 to 1:1. CMC or its metal salt is preferably used.

[0057] When a dried film of a secondary battery negative electrode slurry composition using a combined CMC formed by the combination of the above (A) and (B) is observed with an electron microscope (SEM), as will be further described later in the Examples, the carbon nanotubes (CNTs) are entangled on the surface of the negative electrode active material without agglomeration, thereby obtaining a secondary battery negative electrode slurry composition having a low resistance value when an electrode is formed.

[0058] The total content of these dispersants can be set to a suitable content without particular limitation. Preferably, for high stability and preferred coating viscosity, the content is preferably 0.1 to 2% by mass, more preferably 0.2 to 1% by mass, and more preferably 0.2 to 0.8% by mass relative to the total amount of the slurry composition.

[0059] If the content is less than 0.1 mass %, the effects of the present disclosure cannot be achieved and aggregation and precipitation of active materials and conductive materials may occur. On the other hand, if the content exceeds 2 mass %, the viscosity becomes excessively high and electrodes may not be produced, which is not preferred.

[0060] (Binder ingredients)

[0061] As the binder component, for example, various emulsion-type polymers can be used, specifically, fluorine-based emulsion-type polymers such as polyvinylidene fluoride (PVdF) and polytetrafluoroethylene (PTFE), elastomeric emulsion-type polymers such as ethylene-propylene-diene copolymer (EPDM), nitrile rubber (NBR) and styrene-butadiene rubber (SBR), acrylic emulsion-type polymers, etc. can be used.

[0062] As the polymer, from the viewpoint of conductivity, it is preferable to use an elastic emulsion type polymer, and it is particularly preferable to use a styrene-based elastic emulsion type polymer, and it is particularly preferable to use styrene-butadiene rubber.

[0063] In addition, as the polymer, for example, natural polymers such as polysaccharides and synthetic polymers can be used. Such polymers are sometimes used as thickeners.

[0064] As the polysaccharide, for example, gum arabic, tragacanth gum, guar gum, locust bean gum, alginic acid, carrageenan, gelatin, xanthan gum, welan gum, succinoglycan, diutan gum, dextran, methylcellulose, ethylcellulose, hydroxyethylcellulose, starch glycolic acid, and salts thereof can be used.

[0065] As the synthetic polymer, water-soluble resins such as polyvinyl methyl ether, polyacrylic acid and its salts, polyethylene oxide, vinyl acetate-polyvinyl pyrrolidone copolymer, styrene-acrylic acid copolymer and its salts, isobutylene maleic anhydride copolymer and its salts can be used.

[0066] In addition, as the polymer, nonionic dispersants such as polyalkylene oxide, polyvinyl acetal, polyvinyl ether, chitosan, chitosan, starch, etc. can be used. These polymers are sometimes used as dispersing aids.

[0067] The content of these binder components can be set to a suitable content, and is not particularly limited. Preferably, from the perspective of preferred coating liquid viscosity and electrode stability, its content relative to the total amount of the slurry composition is preferably set to 0.1 to 2 mass %, more preferably 0.2 to 1 mass %, and more preferably 0.2 to 0.8 mass %.

[0068] The balance of the slurry composition for a negative electrode for a secondary battery of the present disclosure may be made of a water-soluble solvent in addition to water (eg, purified water, distilled water, pure water, ultrapure water, tap water, ion-exchanged water, etc.).

[0069] The negative electrode slurry composition for secondary batteries disclosed herein may contain, in addition to the carbon nanotubes, conductive material, negative electrode active material, dispersant and binder components, a pH adjuster, a preservative, a leveling agent, a solid electrolyte material, a release agent, etc., within a range not impairing the effects of the present disclosure.

[0070] (pH adjuster)

[0071] The pH of the slurry composition for a negative electrode for a secondary battery of the present disclosure is preferably 4 to 9 from the viewpoint of corrosion of the current collector and the viewpoint of composition stability.

[0072] As the pH adjuster that can be used, for example, at least one of ammonia, urea, monoethanolamine, diethanolamine, triethanolamine, aminomethylpropanol, sodium tripolyphosphate, alkali metal salts of carbonic acid or phosphoric acid such as sodium carbonate, and alkali metal hydroxides such as sodium hydroxide can be used.

[0073] Examples of the preservative that can be used include organic sulfur-based, organic nitrogen-sulfur-based, organic halogen-based, halogenated allyl sulfone-based, propargyl iodide-based, N-halogenated alkylthio-based, nitrile-based, pyridine-based, 8-hydroxyquinoline-based, benzothiazole-based, isothiazolin-based, dithiol-based, pyridine oxide-based, nitropropane-based, organic tin-based, phenol-based, quaternary ammonium salt-based, triazine-based, thiazine-based, anilide-based, adamantane-based, dithiocarbamate-based, bromoindanone-based, benzyl bromoacetate-based, inorganic salt-based compounds, and at least one selected from ethanol, isopropyl alcohol, propanol, sec-butyl alcohol, tert-butyl alcohol, phenoxyethanol, benzalkonium chloride, and the like.

[0074] In addition, anionic dispersants other than the above CMC may be used as needed within the scope of not impairing the effects of the present disclosure. As anionic dispersants, acrylic resins such as styrene acrylic resins, polyurethane resins, polyester resins, polyvinyl chloride resins, and epoxy resins may be used.

[0075] The negative electrode slurry composition for secondary batteries disclosed in the present invention is a negative electrode slurry composition for secondary batteries containing at least carbon nanotubes, a conductive material, a negative electrode active material, a dispersant and a binder component. The aforementioned dispersant is carboxymethyl cellulose or its metal salt with a mass average molecular weight of less than 300,000 and carboxymethyl cellulose or its metal salt with a mass average molecular weight of 1 million to 3 million. The production thereof can be obtained, for example, as follows: using the following apparatus, in addition to carbon nanotubes, CMC of the above-mentioned characteristics, and water, a water-soluble solvent, a preservative, etc. are added, and the mixture is stirred / mixed and then subjected to a dispersion process to obtain the composition.

[0076] As the above-mentioned manufacturing apparatus, for example, a mixer such as an ultrasonic disperser, a disperser, a homomixer, a rotation and revolution mixer, a Henschel mixer, a planetary mixer, a (high-pressure) homogenizer, a paint conditioner, a colloid mill, a bead mill, a cone mill, a ball mill, a sand mill, a grinder, a pearl mill, a media-type disperser such as an annular gap ball mill, a wet jet mill, a medium-free disperser such as a thin film rotating high-speed mixer, and a dispersing device such as a roll mill can be used for dispersion treatment, but it is not limited to these.

[0077] As a preferable apparatus, a planetary mixer, a bead mill, etc. are preferable from the viewpoint of stability and dispersion efficiency.

[0078] In addition, from the perspective of precipitation stability and coating properties, the slurry composition for the negative electrode of the secondary battery of the present disclosure preferably has a shear rate of 1000 s. -1 The viscosity is 0.1 to 1.5 Pa·s.

[0079] The viscosity can be adjusted by appropriately combining carboxymethyl cellulose having a mass average molecular weight of 1,000,000 to 3,000,000 or a metal salt thereof.

[0080] The slurry composition for a negative electrode for a secondary battery of the present disclosure thus constituted can uniformly distribute the conductive material and the active material when applied to form an electrode, and can form a negative electrode having high stability and low resistance when formed into an electrode. Specific embodiments

[0082] The present disclosure will be described below based on examples, but the present disclosure is not limited to these examples.

[0083] According to each formulation shown in Table 1 below, each negative electrode slurry composition for secondary batteries was prepared by the following preparation method.

[0084] (Examples 1 to 4 and Comparative Examples 1 to 3: Preparation method)

[0085] Carbon nanotubes, acetylene black and graphite as conductive materials, active material particles, binder components, two kinds of CMC, and water were mixed and stirred using a planetary mixer to prepare slurry compositions for negative electrodes for secondary batteries. It should be noted that the styrene-butadiene rubber as a binder was in the state of an emulsion.

[0086] Using the obtained slurry compositions for secondary battery negative electrodes of Examples 1 to 4 and Comparative Examples 1 to 3, the shear rate of 0.2 s was evaluated. -1 , shear speed 1000s -1 The results are shown in Table 1 below:

[0087] (Method for measuring viscosity value)

[0088] The rheometer (MCR302, Anton Paar GmbH cone-plate 2°), and measure the shear rate at 25°C for 0.2s -1 , shear speed 1000s -1 The viscosity values ​​of .

[0089] (pH measurement method)

[0090] The pH at 25° C. was measured using a pH meter F72 (manufactured by Horiba, Ltd.).

[0091] (Method for measuring the resistance value of coating film)

[0092] The obtained slurry for electrode was subjected to measurement of a thin-layer resistor for evaluation of electrical conductivity by the following measurement method.

[0093] The electrode slurry was applied to one side of a PET film (Lumirror #100-T60, Toray Industries, Inc.) using an applicator with a gap of 50 μm, and then dried at 80° C. to measure the resistance of the resulting film. The resistance was measured using a sheet resistance meter with a 4-probe mΩ HiTESTER3227 (manufactured by Hioki Electric Co., Ltd.) with a probe spacing of 10 mm.

[0094] When the sheet resistance is 1.0 kΩ / □ or less, it can be confirmed that the conductivity is excellent.

[0095] (SEM observation method)

[0096] The completed electrode slurry was applied to one side of a PET film (Lumirror #100-T60, Toray Industries, Inc.) using an applicator with a gap of 50 μm, dried at 80°C, cut into a size suitable for a measuring machine, and the surface condition was observed and evaluated according to the following evaluation criteria.

[0097] Evaluation criteria:

[0098] ○: There are no aggregates of carbon nanotubes, and the carbon nanotubes are well entangled with the active material.

[0099] △: Aggregates of carbon nanotubes are still visible, but are not entangled with the active material.

[0100] ×: There are many aggregates of carbon nanotubes, and they are hardly entangled on the surface of the active material.

[0101] (Evaluation method of separation stability)

[0102] The completed electrode slurry was placed in a transparent glass bottle and left at 25°C for 1 month, and the separation stability of the electrode slurry was visually observed. The evaluation was performed according to the following evaluation criteria. In addition, the solid content (%) of the transparent glass bottle portion and the lower portion was calculated.

[0103] Evaluation criteria:

[0104] 〇: Uniform appearance.

[0105] △: Slight separation is observed in appearance.

[0106] ×: Clear separation and precipitation were observed in appearance.

[0107] [Table 1]

[0108]

[0109] *1 to *9 in the above Table 1 are as follows.

[0110] *1: LT-112 (manufactured by Ishihara Industry Co., Ltd.)

[0111] *2: Carbon nanotubes (average outer diameter: 9.5 μm, manufactured by Nanocyl Corporation)

[0112] *3: DENKABLACK (manufactured by Denka Company Limited)

[0113] *4: FS5 (manufactured by East Japan Carbon Co., Ltd.)

[0114] *5: CELLOGEN WS-C (mass average molecular weight: 150,000: manufactured by DKS Co., Ltd.)

[0115] *6: Daicel 1190 (mass average molecular weight 1.17 million: manufactured by Daicel Corporation)

[0116] *7: F800HC (mass average molecular weight 5 million: manufactured by Nippon Paper Co., Ltd.)

[0117] *8: PVP K30 (manufactured by BASF)

[0118] *9: S2910(E)-12-Na (manufactured by JSR Corporation)

[0119] The evaluation results in Table 1 above show that the negative electrode slurry compositions for secondary batteries of Examples 1 to 4 within the scope of the present disclosure can form negative electrodes with high stability and low resistance when forming electrodes without losing the prescribed properties. In contrast, the electrode slurries of Comparative Examples 1 to 3 that are not within the scope of the present disclosure cannot satisfy the above characteristics.

[0120] Industrial Applicability

[0121] The slurry composition for a negative electrode for secondary batteries can form a negative electrode having high stability and low resistance when the electrode is formed, and is particularly suitable for the production of a negative electrode for lithium ion secondary batteries and the like.

Claims

1. A slurry composition for a negative electrode for a secondary battery, characterized in that: The invention contains at least carbon nanotubes, a conductive material, an active material for a negative electrode, a dispersant and a binder component. The dispersant is carboxymethyl cellulose or a metal salt thereof with a mass average molecular weight of less than 300,000 and carboxymethyl cellulose or a metal salt thereof with a mass average molecular weight of 1 to 3 million.

2. The negative electrode slurry composition for secondary batteries according to claim 1, characterized in that: Shear speed 1000s -1 The viscosity is 0.1 to 1.5 Pa·s.

Citation Information

Patent Citations

  • Negative electrode plate for nonaqueous electrolyte solution secondary battery, its manufacturing method, and nonaqueous electrolyte solution secondary battery

    JP2009099441A

  • Negative electrode plate for nonaqueous secondary battery and nonaqueous secondary battery using the same

    JP2012059488A

  • Lithium secondary battery manufacturing method

    JP2013089422A

  • Carbon nanotube dispersion and nonaqueous electrolyte secondary battery

    JP2015195143A